Kualitas Pelayanan pada Perusahaan Transportasi: Realisasi VS Ekspektasi - Yogi Adhitya Pratama; Egi Arvian Firmansyah (Universitas Airlangga, 2019)
This study aims to compare the performance and service expectations from an otobus (PO) company in the city of Bandung. The company is PO Grand Star Holiday Transport. The research is using five dimensions, namely the dimensions of reliability, responsiveness, assurance, empathy and tangibility. The method used in this research is the descriptive method by providing an overview of the level of service quality and the expectations of consumers. The data was collected by the method of field studies conducted by distributing written questionnaires. Based on the results of the study, it is known that the company's service quality is in the good category but it still does not meet the expectations of consumers. In conclution, this reasearch shows that there are things that need to be improved, especially related to the dimensions of empathy and reliability.